2006
DOI: 10.1243/095440505x32913
|View full text |Cite
|
Sign up to set email alerts
|

Bending Under Tension Test with Direct Friction Measurement

Abstract: A special bending-under-tension (BUT) transducer has been developed in which friction around the tool radius can be directly measured when drawing a plane sheet strip around a cylindrical tool pin under constant back tension. The front tension, back tension, and torque on the tool pin are all measured directly, thus enabling accurate measurement of friction and direct determination of lubricant film breakdown for varying normal pressure, sliding speed, tool radius, and tool preheat temperature. The transducer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 1 publication
0
34
0
8
Order By: Relevance
“…On the other hand, Andreasen et al 58 took into account the average friction stress τ and the normal pressure p acting on the contact area between the strip and the die. These values can be calculated as follows:…”
Section: Bending Under Tensionmentioning
confidence: 99%
“…On the other hand, Andreasen et al 58 took into account the average friction stress τ and the normal pressure p acting on the contact area between the strip and the die. These values can be calculated as follows:…”
Section: Bending Under Tensionmentioning
confidence: 99%
“…In this connection a system of test methods representing the varied conditions in sheet metal forming have been developed including simulative tests: Bending-Under-Tension (BUT) [3], Draw-Bead-Test (DBT) [160], Strip-Reduction-Test (SRT) [1,2] as well as process tests: Deep-Drawing-Test (DDT) [2,161] and PUnching-Test (PUT), [158,159]. In order to emulate real production conditions, preheating of the tool temperature to typical production level is possible in all the simulative tests.…”
Section: Alternatives To Dry Film Lubricationmentioning
confidence: 99%
“…Interestingly, the deceleration of ram speed towards the end of the stroke that occurs in the conducted experiments supports the conclusion that punch force signatures can detect lubrication mechanism change. Andreasen et al [13] found that lower sliding speeds in Bending Under Tension tests led to significant friction stresses and lubrication film breakdown, so an increase in punch force should be expected as the ram speed decreases. Such an increase in the punch force signatures is only observed for the fluid lubrication trials, suggesting that lubrication film breakdown is occurring.…”
Section: Discussionmentioning
confidence: 99%